Penentuan Kebutuhan Pompa Air Bersih Fakultas Kemaritiman UNISVET - Suyanto Suyanto (Universitas Ivet, 2021)
Determining the need for clean water needs to be planned properly. In determining the need for clean water, it is necessary to estimate the number of occupants or building users on average every day. On this basis, it is necessary to calculate the average daily water requirement. The determination of the size of the pipes and water pumps also needs to be taken into account based on the consideration of the initial information on the need for water supply. The piping installation and the determination of the pump supplying clean water in the Faculty of Maritime Affairs have not been based on the calculation of the need for clean water at the Faculty of Maritime Affairs. For this reason, this article will be presented calculation of the need for clean water in the Maritime Faculty building, and the specifications of the pump that will need to be used. With the calculation and analysis of the existing data, it is obtained that the average clean water requirement is 3.36 m3/hour in peak conditions of 6.72 m3/hour. The pipe used is PVC with a diameter of 1.5 inches. The pump used is 750Watt of electricity, 6m of suction power and 12m of thrust, and a capacity of 240 lt/min.